Effect of Job Embeddedness on Innovative Work Behavior, Mediating Role of Work Engagement among Banking Sector Employees of Malakand (Pakistan) (Journal of Asian Development Studies, 2025)
This study investigates the effect of job embeddedness on innovative work behaviour, with work engagement as a mediating mechanism, among employees in the banking sector of Malakand, Pakistan. Using a quantitative research design, data were collected from 320 employees across multiple banks through standardised measurement scales. Descriptive, correlation, and regression analyses, alongside structural equation modelling (SEM), were employed to test the hypothesised relationships. The results indicate that job embeddedness significantly enhances innovative work behaviour both directly and indirectly via work engagement. Work engagement partially mediated this relationship, highlighting its role as a psychological mechanism that translates organisational attachment into proactive and creative actions. The findings also suggest that fostering strong interpersonal connections, organisational fit, and meaningful work can promote employee engagement and innovation. This study provides empirical evidence for HR practitioners and managers in designing strategies to strengthen employee embeddedness and engagement, ultimately enhancing innovation in the banking sector. Implications for theory and practice are discussed, and directions for future research are proposed.